Efficacy of Xiaoyao-san preparations in treating Hashimoto’s thyroiditis: a meta-analysis and systematic review - Chengna Wang; Chengna Wang; Wenxin Ma; Lingling Qin; Lingling Qin; Lili Wu; Tonghua Liu (Frontiers in Pharmacology)
ObjectiveTo assess Xiaoyao-san (XYS) preparations’ effectiveness in treating Hashimoto’s thyroiditis.MethodsEight databases were searched for randomized controlled trials (RCTs) comparing XYS preparations to a low-iodine diet (LID), selenium yeast (SY), levothyroxine (LT4), or Ophiocordyceps sinensis (OS) for HT treatment. The datasets from inception to September 2024. Two reviewers independently evaluated literature and research biases. Meta-analysis was done with Revman 5.4. The GRADE technique assessed evidence reliability. Robustness was assessed using sensitivity and trial sequential analysis (TSA).ResultsThis study analyzed seven randomized controlled trials involving 612 patients. Meta-analysis demonstrated that XYS preparations significantly reduced TPOAb levels [SMD = −0.74, 95% CI (−1.02, −0.46), p < 0.00001]. Combining LT4 with XYS preparations resulted in greater TPOAb reduction compared to LT4 alone [SMD = −0.77, 95% CI (−1.06, −0.47), p < 0.00001] and was more effective in lowering TgAb levels [SMD = −0.66, 95% CI (−1.05, −0.26), p = 0.001]. XYSJW outperformed OS in reducing TgAb [SMD = −0.35, 95% CI (−0.58, −0.10), p = 0.005]. Four XYS preparations (XY, HHXY, GQXY, and DZXY) increased FT3 and FT4 levels [SMD = 0.13, 95% CI (0.01, 0.61), p = 0.04; SMD = 0.58, 95% CI (0.12, 1.04), p = 0.01] and decreased TSH [SMD = −0.76, 95% CI (−0.98, −0.54), p < 0.00001]. Subgroup analysis indicated XY significantly improved FT3 and FT4 levels, but XYS preparations combined with LT4 did not enhance FT3/FT4 restoration. XYSJW also did not reduce TSH more effectively than OS. Evidence quality was low or very low. TSA confirmed the pooled effect estimates, with cumulative z-curves for TPOAb, TgAb, and TSH surpassing the benefit threshold.ConclusionCombination therapy with XYS preparations and LT4 may reduce TPOAb, TgAb, and TSH levels in HT patients. XY combined with LID or SY therapy is more effective at restoring FT3 and FT4 levels. While XYSJW outperforms OS preparations in lowering TgAb levels, it may not surpass OS in restoring thyroid hormone levels. Most studies reviewed are of low quality. XYS preparations appear to modulate cytokines by targeting immune markers and reducing inflammation, but their safety profile remains unclear, requiring further robust evidence.Systematic Review Registrationclinicaltrials.gov, identifier CRD42023472233.